In Silico Study of Ethanolic and Methanolic Extracts of Tridax procumbens (Londotan) as Anti-Inflammatory Agents Targeting the COX-2 Receptor - Ishrolana Lutfi Anggraeni; Hosnatul Hasanah; Nur Faizah; Indah Ayu Wulandari; Silvia Kurnia Sari; Mohammad Rofik Usman (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Inflammation is a major pathological process that occurs when the body’s immune system responds to stimuli caused by various injury factors. The incidence of injuries in Indonesia has reached 9.7%, showing an increase compared to 2014 (7.3%) and 2007 (7.9%). One plant that has not been widely utilized as a medicinal agent but is known to possess anti-inflammatory activity is T. procumbens (commonly known as londotan). The aim of this study was to evaluate the interaction mechanisms of the bioactive compounds from T. procumbens with the COX-2 receptor through a molecular docking approach using the receptor structure obtained from the Protein Data Bank (PDB ID: 5IKR). Sodium diclofenac was employed as the positive control to identify potential new anti-inflammatory drug candidates with favorable pharmacokinetic profiles The molecular docking simulation results indicated that Quercetin-3-O-alpha-L-rhamnopyranoside the lowest binding free energy (delta G = ?9.73 kcal/mol) with an inhibition constant (Ki) of 73.71 nM, and formed significant hydrophobic interactions with the native ligand residues LEU B:352, VAL B:523, VAL B:349, and ALA B:527. In terms of pharmacokinetic properties, Quercetin-3-O-alpha-L-rhamnopyranoside demonstrated superior performance compared to sodium diclofenac and the native ligand, suggesting that T. procumbens has promising potential to be developed as an anti-inflammatory drug.